Identifying marks : race, gender, and the marked body in nineteenth-century America - Putzi, Jennifer (University of Georgia Press, 2006)
"What we know of the marked body in nineteenth-century American literature and culture often begins with The Scarlet Letter's Hester Prynne and ends with Moby Dick's Queequeg. This study looks at the presence of marked men and women in a more challenging array of canonical and lesser-known works, including exploration narratives, romances, and frontier novels. Jennifer Putzi shows how tattoos, scars, and brands can function both as stigma and as emblem of healing and survival, thus blurring the borderline between the biological and social, the corporeal and spiritual."--Jacket